1999
DOI: 10.1038/4429
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions on microarrays

Abstract: The structural features of nucleic acid probes tethered to a solid support and the molecular basis of their interaction with targets in solution have direct implication for the hybridization process. We discuss how arrays of oligonucleotides provide powerful tools to study the molecular basis of these interactions on a scale which is impossible using conventional analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
467
2
9

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 701 publications
(498 citation statements)
references
References 35 publications
16
467
2
9
Order By: Relevance
“…Microarray-based expression profile technology is based on hybridisation methods first employed nearly 30 years ago (Southern et al, 1999). RNA from cells are reverse transcribed into cDNAs, which are then fluorescently or radioactively labelled and used to probe a predetermined set of DNAs.…”
Section: Microarray Technologymentioning
confidence: 99%
“…Microarray-based expression profile technology is based on hybridisation methods first employed nearly 30 years ago (Southern et al, 1999). RNA from cells are reverse transcribed into cDNAs, which are then fluorescently or radioactively labelled and used to probe a predetermined set of DNAs.…”
Section: Microarray Technologymentioning
confidence: 99%
“…These spacers are used to reduce steric hindrance caused by oligonucleotide packing at the substrate surface that makes bases near the surface less accessible for hybridization. It has previously been shown that hybridization efficiency can be increased two orders of magnitude by including such spacer arms (Southern et al, 1999). Immediately after arraying, the surfaces are put in a humid chamber at 37°C for 6-24 h. To prevent nonspecific adhesion of sample DNA and of the magnetic beads to the unmodified areas of the gold surface, the arrayed surfaces are also treated with thiolated PEG (O-(2-mercaptoethyl)-o%-methyl-polyethylene glycol 5000, 10 mg/ml in deionized water for 1 h at room temperature).…”
Section: Dna Patterning and Hybridization Assaymentioning
confidence: 99%
“…Glass is preferable as it enables the use of small reaction volumes, permitting a greater number of probes to be applied in a smaller space with low autofluorescence, allowing the simultaneous application of paired fluorophores to a single sample. 13,14 Oligonucleotides of cDNA, typically 20-25 base pairs long, are spotted mechanically onto a silane-coated slide or are synthesized in loco. 15 For analysis using a cDNA microarray it was formerly imperative to employ specific sets of tissue-appropriate cDNA probes generated from the mRNA derived from relevant clones.…”
Section: Molecular Adjuncts To Diagnosis: the Microarraymentioning
confidence: 99%